THE ROLE OF ECOLOGICAL COMPETENCE IN THE MORAL DEVELOPMENT OF MEDICAL EDUCATION STUDENTS - Tursunova Muborak Nurmaxmatovna (Modern American Journals, 2025)
This article analyzes the phraseological units encountered in Togaymurod’s Otamdan qolgan dalalar. The study examines the lexical-semantic features, artistic functions, and the role of these phrases in character creation. The analysis highlights the expressive, emotional, and national-mentality-specific layers of these phrases.
Keywords: phraseology, lexical-semantic analysis, literary text, phrase, emotional connotation, Togaymurod, style.